MORPHOLOGICAL, CHEMICAL, MINERALOGICAL PROPERTIES AND SOIL CLASSIFICATIONS IN SOME TOPOSEQUENS OF MAMUJU DISTRICT WEST SULAWESI - Ida Suryani; Ravika Mutiara; Sri Hajriani AR; Nurul Muchlisah (Universitas Hasanuddin, 2021)
This study determines the morphological, chemical, mineralogical properties, and soil classification in several toposequences in Mamuju District, West Sulawesi. The research method used is a descriptive exploratory method supported by laboratory analysis data. The results showed yellow and brown soil color, clay texture, subangular structure, slightly sticky consistency, and gradually diffuse horizon boundaries. The Cation Exchange Capacity ranges from Medium to high, very low to low base saturation, and low carbon percentage. The topsoil and subsoil mineral content are dominated by clay minerals and other minerals such as biotite, opaque, muscovite, and feldspar. Soil classification is classified into the Udepts Suborder, Great Group Dystrudepts, and Typic Dystrudepts Subgroup (Profiles 1 and 3). In contrast, Profile 2 is classified into Suborder Humult and Great group Haplohumult and Subgroup Typic Haplohumult.